Six Big Losses Method for Management Maintenance on the Coal Feeder Machine PT Indonesia Power - Hatami Zain; Mohamad Jihan Shofa; Heru Winarno; Faishal Ade Hermawan (MultiTech Publisher, 2023)
Indonesia Power Suralaya is a steam power generating company. The coal feeder machine is an auxiliary tool in the steam power plant (PLTU) cycle. The object of this research is the coal feeder machine located in the boiler plant. The coal feeder machine functions to regulate the amount of coal needed to be used as heating fuel in the boiler system. One of the problems with the coal feeder machine is that it is ripped or the belt is torn causing the machine to not operate. This failure or damage causes downtime or the machine stops operating. One of the methods used in this research is the six big losses which find out what types of losses can affect the effectiveness of a machine or component and this method aims to find out what losses affect the effective reduction of a machine's effectiveness. One of the purposes of using six big losses is to find out what losses affect the function and performance of the machine/equipment used and to avoid the six big losses found in coal feeder machines so that the machine avoids stopping suddenly. The purpose of this research is to determine the losses that occur when the machine experiences problems using the six big losses method. The results of calculations using the six big losses method show that the largest loss in equipment failure losses is 1. Keywords: Coal feeder, effectiveness, six big losses